1
You visited us 1 times! Enjoying our articles? Unlock Full Access!
Question

# If $\frac{x}{y}+\frac{y}{x}=-1\left(x,y\ne 0\right)$, the value of x3 – y3 is (a) 1 (b) –1 (c) 0 (d) $\frac{1}{2}$

Open in App
Solution

## $\mathrm{Given}:\phantom{\rule{0ex}{0ex}}\frac{x}{y}+\frac{y}{x}=-1\phantom{\rule{0ex}{0ex}}⇒\frac{{x}^{2}+{y}^{2}}{xy}=-1\phantom{\rule{0ex}{0ex}}⇒{x}^{2}+{y}^{2}=-xy\phantom{\rule{0ex}{0ex}}⇒{x}^{2}+{y}^{2}+xy=0...\left(1\right)\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}\mathrm{Now},\phantom{\rule{0ex}{0ex}}\left({x}^{3}-{y}^{3}\right)\phantom{\rule{0ex}{0ex}}=\left(x-y\right)\left({x}^{2}+{y}^{2}+xy\right)\left(\mathrm{Using}\mathrm{the}\mathrm{identity}:{a}^{3}-{b}^{3}=\left(a-b\right)\left({a}^{2}+{b}^{2}+ab\right)\right)\phantom{\rule{0ex}{0ex}}=\left(x-y\right)×0\left(\mathrm{From}\left(1\right)\right)\phantom{\rule{0ex}{0ex}}=0\phantom{\rule{0ex}{0ex}}\phantom{\rule{0ex}{0ex}}\mathrm{Hence},\mathrm{the}\mathrm{correct}\mathrm{option}\mathrm{is}\left(\mathrm{c}\right).$

Suggest Corrections
1
Join BYJU'S Learning Program
Related Videos
x^2 - y^2
MATHEMATICS
Watch in App
Join BYJU'S Learning Program